Strengthening Medication Adherence Practices in Chronic Disease Patients-Clinical Pharmacist Driven Focused Approach - Wadhwa, Tarun; Jalal, Hanin; Merghani, Madlin; Shehhi, Aaesha Al (Indian Journal of Pharmacy Practice)
Medication adherence practices are becoming an important concern for healthcare professionals and patients. Globally, medication non-adherence is quite prevalent and affecting the healthcare of patients leading to inadequate response to treatment and augmented healthcare cost. With the advent of improvised practices in clinical care, patient-related problems mainly non-adherence have been conquered to a greater extent. Clinical practice is changing over a period contributing more towards patient care. Expansion of clinical pharmacy activities with a focused approach towards patient care especially optimized pharmaceutical care has seen a tremendous revolution in modern era. According to a study, 50% of patients with chronic conditions are not adherent to their medications with an estimated adherence range of 17% to 80%. Drugs used for asymptomatic chronic conditions have been shown to have low adherence rates. Risk of non-adherence has been shown to be rapidly increasing with the initiation of chronic medication especially in the first year of its commencement. Medication nonadherence is one of the most significant reason for inadequate response to drug therapy, initial hospitalization, frequent hospital visits and Adverse Drug Events (ADEs) leading to inappropriate therapeutic outcome and in turn, raised healthcare cost. Due to lack of sufficient support or appropriate channel, there is a growing concern for healthcare professionals to take initiative and strengthen the medication adherence practices. Clinical pharmacist’s initiatives in this direction has been appreciated and documented with clinically proven evidence of better impact on patient’s health-related quality of life. Patient tools such as pill reminders, alarming system, dose indicator, standard day-wise schedule, colorful pills etc. have brought pill revolution with the intention of improvising medication adherence practices worldwide. The current requirement is to monitor such patients in clinical practice and encourage them to comply with medication-related instructions and adhere to their medication schedule at the most.
Keywords: Adverse drug event; Medication Compliance; Medication Non-Adherence; Polypharmacy; Prevalence.